The Role of Changes in Customer Behavior on Smart Marketing Strategies in The Post-Covid Pandemic Era - Maria Sugiat (Journal of Economics and Business UBS, 2021)
Introduction: At the beginning of 2020 COVID-19 virus swept the globe in a matter of months, jeopardizing lives, upending businesses, and setting off a worldwide economic slump. To suppress the spread of Covid-19, the government of Indonesia implemented "Restrictions on certain activities of residents in an area suspected of being infected with a disease and/or contaminated in such a way as to prevent the possibility of spreading the disease Objective: -19 pandemic. Customers have often used communication technology so that they can take advantage of existing online applications to fulfill their basic daily needs.  Covidexplorative research using qualitative and cross sectional research methods is used to explain the relationship between changes in consumer behavior and marketing strategy.Data analysis using the Spradley technique with domain and taxonomy analysis  Results: The results show that the customer's online shopping pattern will continue until period no. next rm. It is based on customer characteristics and technocultural theory. According to one major retailer in Indonesia, there was an increase in transactions during social distancing by an average of 45%. Online shopping and home delivery services have also become consumer demand. Conclusion: 1.  In the post-pandemic covid-19, the pattern of spending on basic needs will not change due to the convenience of using the internet to do the shopping and there are online services. 2.  Since there are online services to do shopping from their home and office, there are no changes on the post-pandemic covid-19. 3.  The internet of things causes buying behavior to change based on the relationship between technology & culture. However, this change has occurred since the era of the covid-19 pandemic 4. Youth in Indonesia is recorded at 24% of the total population based on demographics with around 64 million people in the number of youth or what is commonly referred to as the millennial generation. 5. The shopping behavior post-covid-19 pandemic can be expected that consumers to shop online will continue to increase until the new normal era, especially for necessities and entertainment since there is millennial generations growth. 6. Since the buying behavior of the millennial generation will continue until the next normal, the marketer needs an adaptive marketing strategy called smart marketing. It is the term of hybrid marketing with a combination of the supply chain, marketing & e-commerce.